Case Report: Intradural gout tophi without systemic gout symptoms - Qing, Peidong; Xie, Shiming; Feng, Chaoqun; Xu, Hongda; Zhao, Shengxin; Zhang, Lei; Deng, Haitao; Wang, Yehui; Hu, Youpeng (Frontiers in Surgery, 2025)
BackgroundGout is a common disease; however, a gout tophus occurring within the spinal dura is exceedingly rare, with only two cases reported to date.Case presentationWe report the case of a 70-year-old female who presented with lower back pain, right radicular pain, and numbness in the perineal area. Magnetic resonance imaging and computed tomography scans revealed a calcified intradural lesion at the L3 level. The diagnosis of the lesion was not definitive because the patient had no history of gout or manifestations of systemic gout. Surgical removal of the intradural lesion followed by pathological examination confirmed gouty tophi. The postoperative recovery was good, and the patient experienced substantial relief from pain and numbness.ConclusionThis is the third documented case of gout tophi occurring within the spinal dura. In a literature review, it was found that none of these three patients with intradural gouty tophi had systemic gout manifestations or hyperuricemia, which is a crucial finding. As it is challenging to diagnose intradural gout, awareness among physicians must be increased to optimize the treatment of, and outcomes for, these patients.